Representasi Nilai Kejujuran Dalam Film: Analisis Semiotika Roland Barthes Atas Film “Kulari Ke Pantai” Karya Riri Reza - Madani Matadian; Sri Hastjarjo (Universitas Sebelas Maret (UNS), 2024)
Film is one of the mass communication media that has three main roles and functions, namely as entertainment, education, and information that reaches the most social segments that can be enjoyed by anyone without age restrictions. Movies are also often a means of transmitting messages with implied meanings that communicators want to convey to the general public (Ardianto, 2007). However, the production of children's films in Indonesia is not as vibrant as the production of films with other segments. In 2018, the phenomenon of globalization has penetrated the level of children aged 5-10 years which has many negative impacts, one of which is the decline in moral values. Thus, Miles Films released the movie Kulari ke Pantai which aims to instill moral values in school-age children.Kulari ke Pantai depicts the reality that occurs in various layers of society, where moral values become a noble value that applies in Indonesia. One of the moral values that appear in Kulari ke Pantai is the moral value of honesty represented through non-verbal and verbal signs such as dialog, visual signs, property, cinematography, background music, body language of each character, and others. The method used in this research is Roland Barthes' semiotic qualitative analysis method through the three elements he put forward, namely denotation meaning (actual meaning), connotation (meaning back to denotation meaning that has an intrinsic message), and myth (connotation meaning of joining culture).